Analysis of statistical resolution limit based on Rao test - Minhong SUN; Yanfang LIU; Hua ZHONG; Jianrong BAO (Dianxin kexue)
Since the approach of analyzing statistical resolution limit (SRL) based on generalized likelihood ratio test (GLRT) has the problems of high computational complexity and isn’t easy to get the analytical formula of the detection statistics,a method for the analysis of the SRL based on Rao test was proposed.The unidimensional SRL of azimuth under the cases of known and unknown noise variance,two-dimensional SRL of azimuth and elevation under the case of known noise variance were analyzed.The Rao test detection statistic and the minimum SNR required for the corresponding SRL were derived,the detection performance and the computational complexity of the Rao test were analyzed and compared with the GLRT method.Simulation results verify the validity of the Rao test.